Creation, destruction and job reallocation in Colombian manufacturing sector (2013)
This paper analyzes the characteristics of job flows in the Colombian manufacturing sector between 1994 and 2009, at the industry group level and for the occupational categories. The results suggest high levels of job creation and job destruction in manufacturing firms, which are not usually evident in the figures of net employment growth. Similarly, we find that job creation and job destruction are persistent. Finally, the results at a disaggregated level indicate significant differences by industry group and occupational category.